The Impact of Different Lighting with the Use Of Palm Oil Liquid Waste for the Production of Microalgae Chlorella sp. at Ptpn V Sei Galuh, Kampar Regency, Riau Province - Tuti Maisarah Br. Siregar; Tengku Dahril; Asmika Harnalin Simarmata (Berkala Perikanan Terubuk, 2023)
Oil palm liquid waste contains N (nitrate) and P (phosphate) which can be utilized for the growth of microalgae. Utilization of palm oil liquid waste using microalgae has been widely carried out. One of the microalgae that has potential as phycoremediation is Chlorella sp. Factors that affect the growth of Chlorella sp. cells, are the intensity of light and nutrients. This study used the same concentration of palm oil wastewater, namely 25% with different light intensities. A research aims to determine the best light intensity in producing Chlorella sp., carried out in December 2022-January 2023. The method used is the experimental method with Completely Randomized Design (CRD) with 4 treatments, namely: light intensity 6 Lux, light intensity 1443 Lux , light intensity 2748 Lux, and light intensity 3171 Lux. Water quality parameters measured were cell abundance (once/two days), Chlorella sp. biomass (in the exponential phase), temperature, pH, dissolved oxygen (DO) (once/ two days) and nitrate, phosphate (at the beginning, exponential phase and at the end). study). The results showed that the abundance of cells during this study ranged from 0.70 x 106 - 1.98 x 106 cells/ml and the biomass ranged from 0.11-0.29 g/L. The results of water quality measurements are temperatures ranging from 27℃-31.30℃, pH ranging from 7-8, dissolved oxygen 6.06 mg/L-8.66 mg/L, nitrate concentrations were 9.21 mg/L-9.27 mg/L and phosphate concentrations 3.19 mg/L-3.26 mg/L. Water quality parameters in this study such as temperature, pH, dissolved oxygen (DO), nitrate and phosphate are still classified as capable of supporting growth Chlorella sp. Based on the data above the best light intensity for culture Chlorella sp., is 3171 Lux